Analisis Pengaruh Modal, Tingkat Upah dan Teknologi Terhadap Penyerapan Tenaga Kerja Serta Produksi Pada Industri Kerajinan Batako Di Kecamatan Mengwi Kabupaten Badung - Putri, Agnes Febrina; Kesumajaya, I Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 3, Maret 2017 (pp. 286-471), 2017)
The purpose of this study was to analyze and determine 1) The direct effect of capital, wages and technology on employment, 2) The direct effect of capital, wages and technology to the production, 3) The direct effect of employment on production, 4) Influence indirectly, capital, wages and technology to the production through employment. Based on the research results directly be concluded that the capital, wages and technology positive and significant impact on employment in the craft industry brick Mengwi. Variable capital, wages, technology and employment and significant positive effect on industrial production in craft brick Mengwi Badung regency. While the variable indirect where the capital, wages and technology does not affect the production indirectly through labor absorption. So absorption of labor not as an intervening variable that mediates the variable capital, wages and technology to production.
Keywords: Modal; Tingkat Upah; Penyerapan Tenaga Kerja; Produksi